Barriers and facilitators to medication adherence: a qualitative study with general practitioners - Marja Airaksinen; Kirsi Kvarnström; Helena Liira (BMJ Open)
Background General practitioners (GPs) manage the drug therapies of people with chronic diseases, and poor adherence to medication remains a major challenge.Objective This qualitative study examined GPs’ insights into non-adherence and ways of overcoming this problem.Methods We ran four focus groups comprising 16 GPs at the Kirkkonummi Health Centre (Southern Finland). Interviews were audiotaped, transcribed verbatim and analysed by inductive content analysis.Main results The two main themes in the discussions with the GPs were non-adherence in the care of chronic disease and increased need for medicine information. The medication management challenges identified were related to: patient-specific factors, the healthcare system, characteristics of drug therapies and the function and role of healthcare professionals as a team. To improve the situation, the GPs offered a number of solutions: improved coordination of care, better patient education and IT systems as well as enhanced interprofessional involvement in the follow-up of patients.Discussion and conclusions With an ageing population, the GPs were increasingly confronted with non-adherence in the care of chronic diseases. They had mostly a positive attitude towards organising care in a more interprofessional manner. To support medication adherence and self-management, the GPs appreciated pharmacists’ assistance especially with patients with polypharmacy and chronic diseases.